Pemahaman Akuntansi Syariah oleh Pelaku Usaha Mikro dan Kecil: Studi Deskriptif di Kabupaten Bengkalis - Novita; Fitri Indah Sari (CV. ALIM'SPUBLISHING, 2024)
Understanding sharia accounting is an important aspect for Micro and Small Enterprises (MSEs) in managing finances in accordance with sharia principles. This research aims to analyze the level of understanding of sharia accounting by MSEs in Bengkalis Regency. This research uses a descriptive approach with data collection techniques in the form of questionnaires, interviews and documentation. The research results show that the majority of MSEs have an understanding of sharia accounting at a basic level, with the main obstacles being a lack of formal knowledge, minimal training and low financial literacy. This study provides recommendations for improving sharia accounting training for MSEs and provides practical sharia-based guidance to help them manage their finances better.